1cube+2cube+3cube+4cube=?square
Answers
Answered by
6
for nth term to find ..Proof by mathematical induction.
When n = 1 the result is clear, 13 = 12
Assume the result is true for n = k, that is
13 + 23 + 33 + 43 + ... k3 = (1 + 2 + 3 +...k)2Let n = k + 1, then 13 + 23 + 33 + 43 + ... n3 = 13 + 23 + 33 + 43 + ... + (k+1)3 = (1 + 2 + 3 + ... + k)2 + (k+1)3 = (k(k+1)/2)2 + (k+1)3 = (k2 (k+1)2)/4 + (k+1)3 = (k+1)2/4 (k2 + 4k + 4) = ((k+1)2 (k+2)2)/4 = ((k+1)(k+2)/2)2 = (1 + 2 + 3 + ... + (k+1))2
Thus 13 + 23 + 33 + 43 + ... n3 = (1+2+3+...n)2for all positive intergers n.
When n = 1 the result is clear, 13 = 12
Assume the result is true for n = k, that is
13 + 23 + 33 + 43 + ... k3 = (1 + 2 + 3 +...k)2Let n = k + 1, then 13 + 23 + 33 + 43 + ... n3 = 13 + 23 + 33 + 43 + ... + (k+1)3 = (1 + 2 + 3 + ... + k)2 + (k+1)3 = (k(k+1)/2)2 + (k+1)3 = (k2 (k+1)2)/4 + (k+1)3 = (k+1)2/4 (k2 + 4k + 4) = ((k+1)2 (k+2)2)/4 = ((k+1)(k+2)/2)2 = (1 + 2 + 3 + ... + (k+1))2
Thus 13 + 23 + 33 + 43 + ... n3 = (1+2+3+...n)2for all positive intergers n.
ramchandramkatpe69bu:
1cube+2cube=1+2square =3square
Similar questions